(untitled) (Al-Qamar, 2023)
The concept of Tawheed, or the oneness of Allah, is central to Islamic beliefs. Within Tawheed, Tawheed Ruboobiyah t specifically emphasizes Allah’s role as the supreme master and sustainer of all creation. This article examines how the Quran employs various rhetorical devices and linguistic techniques to reinforce this belief in the Lordship of Allah. By utilizing different stylistic features such as metaphors, repetition, rhyme, and others, the Quran not only provides logical arguments for Tawheed Ruboobiyah, but also showcases the eloquence and literary artistry of the holy text. The combined use of rational proofs and aesthetic elements engages readers intellectually and emotionally, encouraging deep reflection on this profound theological concept. This article analyzes the key verses related to Tawheed Ruboobiyah, highlighting the effective use of language in conveying its meaning and significance. It demonstrates how the Quran’s eloquence stems from both its substantive message and artistic expression, working in unison to firmly establish faith in the oneness and lordship of Allah.